Short-term Effect of the Semirecumbent Position on Oxygen Saturation and Respiration Rate in Pediatric with Oxygenation Problem - Mawaddah, Ely; Nurhaeni, Nani; Wanda, Dessie; Wanda, Mardiatun; Utami Ningsih, Mira (International Journal of Psychosocial Rehabilitation, 2024)
Objective: Oxygen is a basic physiological need for the survival of human life. Pediatric patients with oxygenation problems need an ideal position to promote necessary oxygen saturation and normal respiration rate. This study aims to identify the effect of semi recumbent position on the oxygen saturation and respiration rate of pediatric patients with oxygenation problem. Method: The study design was a quasi-experimental with a pre-posttest control group design. Forty pediatric patients with oxygenation problems were selected using consecutive sampling and divided into two groups: semi recumbent (n=20) and control (n=20). Statistical analysis was conducted using the Wilcoxon test, Paired t-test, and Mann-Whitney test. Results: A significant difference in the oxygen saturation level was found in the semi recumbent group after 1 hour of semi recumbent positioning. There was no significant difference in the respiration rate before and after intervention in the two groups after 1 hour of positioning. Conclusions: The semi recumbent position can be applied to improve the oxygenation status of pediatric patients with oxygenation problem in a short-term period. Nurses should teach the family how to position pediatric patients with oxygenation problem during their hospitalization.